Factors associated with food safety compliance among street food vendors in Can Tho city, Vietnam: Implications for intervention activity design and implementation - Ba Huynh-Van; Vy Vuong-Thao; Tuyen Huynh-Thi-Thanh; Sinh Dang-Xuan; Tung Huynh-Van; Loan Tran-To; Nguyen Nguyen-Thi-Thao; Cuc Huynh-Bach; Hung Nguyen-Viet (Springer, 2022)
Background Street food plays a valuable role in several Asian countries including Vietnam. Improving the safety of street food is an important responsibility for many local food authorities. This study aims to characterize the business profile of fixed and mobile street food vendors, and to compare their compliance with the food safety criteria. Methods A cross-sectional study was conducted using a questionnaire and observational checklist to assess the ten Vietnamese food safety criteria prescribed under Decision No. 3199/2000/QD-BYT for street food vendors in Can Tho city. A total of 400 street food vendors, composed of fixed and mobile vendors, in urban areas of the city were randomly selected for the survey. Results The study showed significant differences between the two types of street food vendors in educational level (p = 0.017); business profile, including types of foods vended, area in use, number of employees, training in food safety, and business registration paperwork; and the status of compliance with the ten-food hygiene and safety criteria (p < 0.01). Poisson regression analysis found that education attainment (IRR = 1.228, p = 0.015), food safety training (IRR = 4.855, p < 0.01), total business capital (IRR = 1.004, p = 0.031) and total area in use (IRR = 1.007, p = 0.001) appeared to be significantly positively associated with food safety and hygiene compliance. In contrast, mobile vending type was negatively associated with the likelihood of adhering to the ten criteria (IRR = 0.547, p = 0.005). Conclusions These findings emphasize the need for training and education programs to improve food safety knowledge and practice among street food vendors. Basic infrastructure and services, especially clean water, proper sanitation, and waste disposal facilities, should be provided to help street food vendors better practice food safety and hygiene regulations.